Application Of Module Educational Technology in Teaching Economic and Social Geography in Surkhandarya Region - Turopova Saida Normurod Kizi (Genius Journals, 2021)
Application of modular educational technology in teaching economic and social geography in Surkhandarya region, which considers modular teaching methods.
Keywords: Geography education; school geography; pedagogy and technology; module